Incidence, surgical eligibility and outcome of spontaneous intracerebral haemorrhage in Southwest Finland – A retrospective study - Lehto, Sami; Sajanti, Antti; Hellström, Santtu; Koskimäki, Fredrika; Srinath, Abhinav; Bennett, Carolyn; Carrión-Penagos, Julián; Cao, Ying; Jänkälä, Miro; Girard, Romuald; Rinne, Jaakko; Rahi, Melissa; et al. (Elsevier, 2025)
Introduction Spontaneous intracerebral haemorrhage (sICH) is a major cause of morbidity and mortality. Large-scale trials have shown neutral outcomes for surgical interventions. The recent trial suggested functional benefits from surgical intervention. Surgical treatment for sICH is likely increasing. Research question To determine the incidence of sICH in Southwest Finland, standardized to the European population, and to identify the proportion of large sICH patients eligible for surgery based on previously published trial criteria. We also examined factors associated with outcomes, including the effects of anticoagulant and antithrombotic medications. Material and methods A retrospective clinical study identified 596 ICH cases treated at Turku University Hospital (2018–2019), of which 286 were supratentorial sICHs. Variables were analysed using a t-test, chi-squared or Fisher's exact test. A multivariate logistic modelling was performed to evaluate outcome differences. Results The sICH incidence was 29.9/100,000 persons per year, with the highest European population age and sex standardized rates in individuals over 80 years old (110/100,000 males, 142/100,000 females). The incidence of sICH patients meeting surgical criteria was 2.7/100,000 persons per year. Out of 286 patients, 26 were eligible for surgery and had unfavourable outcomes (p = 0.0049). Multivariate analysis indicated a significant decrease in favourable outcomes with warfarin (p = 0.016, OR 0.42) and direct-acting anticoagulants (DOACs) (p = 0.034, OR 0.38), while antithrombotic medications showed no significant effect. Discussion and conclusion We identified comparable incidence of sICH as European average. A small proportion of sICH cases were identified to be candidates for surgical intervention. Anticoagulants were associated with increased risk of unfavourable outcomes.